A Phase I Study of 7-t-Butyldimethylsilyl-10-Hydroxycamptothecin in Adult Patients with Refractory or Metastatic Solid Malignancies - Arnold, Susanne M.; Rinehart, John J.; Tsakalozou, Eleftheria; Eckardt, John R.; Fields, Scott Z.; Shelton, Brent J.; DeSimone, Philip A.; Kee, Bryan K.; Moscow, Jeffrey A.; Leggas, Markos (Clinical cancer research, 2010)
Purpose: 7- t -Butyldimethylsilyl-10-hydroxycamptothecin (AR-67) is a novel third generation camptothecin selected for development based on the blood stability of its pharmacologically active lactone form and its high potency in preclinical models. Here, we report the initial phase I experience with i.v. AR-67 in adults with refractory solid tumors. Experimental Design and Methods: AR-67 was infused over 1 hour daily five times, every 21 days, using an accelerated titration trial design. Plasma was collected on the 1st and 4th day of cycle 1 to determine pharmacokinetic parameters. Results: Twenty-six patients were treated at nine dosage levels (1.2-12.4 mg/m 2 /d). Dose-limiting toxicities were observed in five patients and consisted of grade 4 febrile neutropenia, grade 3 fatigue, and grade 4 thrombocytopenia. Common toxicities included leukopenia (23%), thrombocytopenia (15.4%), fatigue (15.4%), neutropenia (11.5%), and anemia (11.5%). No diarrhea was observed. The maximum tolerated dosage was 7.5 mg/m 2 /d. The lactone form was the predominant species in plasma (>87% of area under the plasma concentration-time curve) at all dosages. No drug accumulation was observed on day 4. Clearance was constant with increasing dosage and hematologic toxicities correlated with exposure ( P < 0.001). A prolonged partial response was observed in one subject with non–small cell lung cancer. Stable disease was noted in patients with small cell lung cancer, non–small cell lung cancer, and duodenal cancer. Conclusions: AR-67 is a novel, blood-stable camptothecin with a predictable toxicity profile and linear pharmacokinetics. The recommended phase II dosage is 7.5 mg/m 2 /d five times every 21 days. Clin Cancer Res; 16(2); 673–80